Behavioral Intention Analysis on Pet Caring in Jakarta - Ujang Sumarwan; Tiara Putri Sajuthi; Netti Tinaprilla (Indonesian Journal of Business and Entrepreneurship (IJBE), 2019)
The aim of the study was to explain the relationship between attitudes and interests in caring for pets. The theoretical basis of this research is Theory of Planned Behavior (TPB). This study used a survey and sampling method conducted at several animal clinics in Jakarta. The number of samples obtained in this study amounted to 178 respondents selected by convenience sampling method using questionnaires and direct interviews. Data analysis using SEM method. The results showed that the attitude toward behavior and perceived behavior control had a significant effect on the behavior intention. This indicates that the more profits a pet owner earned in maintaining an animal, the more it will encourage interest in caring for pets better. The managerial implications for animal care product and service providers are to create a variety of products and develop a business for animal health care and services.Keywords: pets, attitude, behavior intention, theory of planned behavior